The illustrated A brief history of time - Hawking, Stephen, 1942-2018. (New York : Bantam Books, 1996)
The book was on the cutting edge of what was then known about the nature of the universe, but since that time there have been extraordinary advances in the technology of observing both the micro- and the macrocosmic worlds. These observations have confirmed many of Professor Hawking's theoretical predictions in the first edition of his book, including the recent discoveries of the Cosmic Background Explorer satellite (COBE), which probed back in time to within 300,000 years of the universe's beginning and revealed wrinkles in the fabric of space-time that he had projected. Eager to bring his original text the new knowledge revealed by these many observations, as well as his most recent research, for this expanded edition Professor Hawking has prepared a new introduction to the book, written an entirely new chapter on the fascinating subject of wormholes and time travel, and updated the original chapters. This edition is enhanced throughout with more than 240 full-color illustrations, including satellite images, photographs made possible by spectacular technological advances such as the Hubble Space Telescope, and computer-generated images of three and four dimensional realities.
Our picture of the universe -- Space and time -- The expanding universe -- The uncertainty principle -- Elementary particles and the forces of nature -- Black holes -- Black holes ain't so black -- The origin and fate of the universe -- The arrow of time -- Wormholes and time travel - The unification of physics -- Conclusion : Albert Einstein, Galileo Galilei, Isaac Newton.
"A Labyrinth book"--T.p. verso.
Originally published: A brief history of time. New York : Bantam Books, 1988.
Includes index.
Keywords: Cosmology